ANALISIS KESESUAIAN PENERAPAN PSAK NO. 46 TENTANG PAJAK PENGHASILAN TERHADAP PAJAK TANGGUHAN: 1-15 - Wigiyanti Wigiyanti; Ashar Basyir; Erny Pratiwi; Windi Astuti; Yunni Yuniawaty (Jurnal Aplikasi Perpajakan, 2026)
This study aims to analyze the implementation of Statement of Financial Accounting Standards (PSAK) No. 46 concerning Income Taxes at PT Jasa Marga (Persero) Tbk during the 2021–2023 period. The study employed a qualitative descriptive approach using secondary data obtained from the company's consolidated financial statements, Notes to the Financial Statements, PSAK No. 46, and applicable tax regulations. Data were collected through documentation, while data analysis was conducted using a descriptive analysis method by comparing the company's accounting practices with the provisions of PSAK No. 46, particularly regarding the recognition, measurement, presentation, and disclosure of deferred taxes. The findings indicate that PT Jasa Marga (Persero) Tbk has adequately implemented PSAK No. 46 in the preparation of its financial statements. The company has consistently presented and disclosed deferred tax assets and deferred tax liabilities in accordance with the applicable accounting standards. Deferred taxes arose from temporary differences related to long-term employee benefit expenses, allowance for impairment losses on receivables, lease liabilities, as well as differences between accounting and tax treatments of certain transactions. Deferred tax liabilities increased throughout the study period; however, this increase did not adversely affect the company's financial performance, as reflected in the growth of profit before tax, total assets, and total equity.